Curriculum and Character Education: - Mokh. Iman Firmansyah; Sofyan Sauri; Aceng Kosasih (Perhimpunan Intelektual Muslim Indonesia, 2021)
This research is motivated by the phenomenon of the low character of students in responding to 21st-century globalization. Because of this, it is important to ask whether curriculum policies have prepared students to be adaptive to these dynamics. This article aims to analyze the character content and the gradations of student social development in the domain of attitudes in the applicable educational curriculum in Indonesia. This study used a qualitative content analysis method with a directed type design and a framework of eight character strengths that took the coding, theoretical approach, findings, and analysis stages of the Regulation of the Minister of Education and Culture Republic of Indonesia document number 20 of 2016 concerning Basic and Secondary Education Graduate Competency Standards (SKL). The research found: first, the character content is in the attitude domain; spiritual and social, aimed at shaping the character strength of students to become religious, honest, caring, lifelong learners, and physically and mentally healthy; second, the gradation of student social development still focuses on real social development, and has not included the gradation of virtual social development of students as an effort to respond to 21st-century globalization. Therefore, this study recommends the Indonesian government revitalize the character content of SKL in educational curriculum policies by considering two forms of gradation of both real and virtual social development of students as the next generation of the nation.